Potassium and magnesium fertilizers on banana in Uganda: yields, weevil damage, foliar nutrient status, and DRIS analysis - Smithson, P.C.; McIntyre, B.D.; Gold, Cliford S.; Ssali, H.; Night, G.; Okech, S. (Springer, 2004)
Low soil fertility and pest pressure are two causes of the decline in banana (Musa AAA) production in central Uganda. Foliar analysis by the Diagnosis and Recommendation Integrated System (DRIS) pinpoints K and Mg as the most limiting nutrients. This study tested the effects of K and Mg additions on plant performance and weevil damage for 2.75 yr, at Buligwe in central Uganda and Muyogo in southwest Uganda. All treatments received 25 kg P ha–1 and 100 kg N ha–1 annually, while K and Mg were applied (kg ha–1) at 0 K–0 Mg, 100 K–0 Mg, 100 K–25 Mg and 100 K–50 Mg. Fresh fruit yields (Mg ha–1 yr–1) ranged from 3.2 to 5.0 at Buligwe and 14.4 to 18.9 at Muyogo, with similar treatment trends at both sites. The 100 K–0 Mg treatment produced higher yields than no-K control (p = 0.022 for the combined dataset). Yields with K+Mg tended to be lower than with K only, though not significantly different. Foliar nutrient concentrations were little affected by treatments, but varied substantially among sample dates. With increasing cumulative rainfall between foliar samplings, foliar P declined (p = 0.077), K declined (ns), and Ca and Mg increased (p = 0.02 to 0.03). Weevil damage was higher at Buligwe, but was little affected by K and Mg treatments at either site.